The Dialogue between Prophet Sulaiman A.S. and The Hoopoe in QS. An-Naml (Analysis of Contextual Meaning) - Hasanuddin, H. Muh. Iqbal; Hamsa; Adawiyah, Rabiya Tul; Susanti, Rina; Riyadi, Agus (Faculty of Ushuluddin, Adab, and Humanities Universitas Islam Negeri Salatiga, 2024)
The purpose of this research is to know the Dialogue between Prophet Sulaiman and the Hoopoe in QS. An-Naml. This research is qualitative descriptive research. As for the approach used by the researchers, it is a linguistic-semantic approach by analyzing the problems to be studied. The data collection technique is carried out through documentation by means of searching the research data of the library to obtain scientific information collected through the study of literature as a reference to the problem considered appropriate, namely by searching for data related to the title of the researcher. In analyzing data, researchers use qualitative methods. The results suggest that there are 7 sentences that become direct dialogue and 2 sentences which become indirect dialogue. The researchers also found 8 passages, of all these passages there are some sentences whose meaning shape is contextually influenced by the context of the situation and context of language.